Evaluation of a Local Clay as a Dehydration Catalyst - Susan A. Ali; Maha K. El-Aiashy; Zita S. Ayad (Adsorption Science & Technology)
Since Egypt is rich in natural clays, they can be used as a cheap local catalyst for dehydration instead of importing synthetic catalysts. Samples from Wadi El Hai Helwan were studied for this purpose in the raw and activated forms. Activation included either thermal activation by calcination of the clay in a stream of dry air at different temperatures or chemical activation by treatment with different concentrations of sulphuric acid solution. The dehydration activities of the prepared clay catalysts were studied using absolute ethyl alcohol. The optimum conditions for activation were obtained on treating Helwan raw clay with 20% sulphuric acid solution at 104°C at an acid solution/clay ratio of 1.5:1 by weight, followed by calcination at 500°C. The activation energy for this reaction on Helwan clay was estimated as equal to 17.5 kcal/mol.